Perspectives for health technology assessment: Perspectivas para la Evaluación de Tecnologías en Salud - Tolentino Silva, Marcus (2019)
An unplanned health care system is like a paper boat carried by a slowly sinking current. In times of disinformation and excessive distraction, investing in better facts on health technology assessment (HTA) will enable more active actions rather than reactive to the market dynamics. This paper aims to raise some reflections on HTA in terms of political context, health technologies and epidemiological priorities. The perspective of HTA is context dependent, intrinsic to its political and institutional articulation. At the moment, the paradox is to maintain a specialized structure in the face of economic austerity policies that reduce health resources, and a scenario of greater interest in raising public funds by the private sector. Particularly in Brazil, HTA will also have to deal with the gradual shift from a universal health system to a minimum portfolio of services offered by the private sector. The public sector will be requested for very expensive technologies, usually by judicial measures. The precariousness of work relationships will influence HTA workers because they will not have a link and identity with the health system. Thus, there will be more productive and less reflective HTA processes. The context of greater dependence on the private market will allow new problems with medical technologies to emerge, such as the opioid crisis in the United States.